Empowering SME Entrepreneurs: Exploring E-Mind and Financial Self-Efficacy - Yusnita*, Maya; Wardhani, Rulyanti Susi; Yunita, Anggraeni (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This study aims to analyze the readiness of SME entrepreneurs in Pangkal Pinang for digital entrepreneurship acceleration and global expansion, taking into consideration the perspectives of Entrepreneurial Mindset (E-Mind) and Financial Self-Efficacy. Data collection was conducted through surveys with in-depth interviews and questionnaires administered to SME entrepreneurs in Pangkal Pinang. Data analysis used a quantitative descriptive approach with IBM SPSS software. The research findings reveal that SME entrepreneurs in Pangkal Pinang possess a strong Entrepreneurial Mindset (E-Mind), as evidenced by their consistent initiative-taking and responsibility for their actions. They are also adept at recognizing and capitalizing on opportunities for business development. The study further highlights the favorable Financial Self-Efficacy among SME entrepreneurs in Pangkal Pinang, characterized by their confidence in financial management and belief in their ability to achieve financial goals in business management.Keywords: E-Mind; Financial Self-Efficacy; Digital Marketing; Financial Technology; Digital Leadership